Machine learning models in heart failure with mildly reduced ejection fraction patients - Zhao, Hengli; Li, Peixin; Zhong, Guoheng; Xie, Kaiji; Zhou, Haobin; Ning, Yunshan; Xu, Dingli; Zeng, Qingchun (Frontiers in Cardiovascular Medicine, 2022)
Objective: Heart failure with mildly reduced ejection fraction (HFmrEF) has been recently recognized as a unique phenotype of heart failure in current practical guideline. However, risk stratification models for mortality and HF re-hospitalization are still lacking. This study aimed to develop and validate a novel machine learning (ML)-derived model to predict the risk of mortality and re-hospitalization for HFmrEF patients. Methods: We assessed the risks of mortality and HF re-hospitalization in HFmrEF (45%-49%) patients enrolled in the TOPCAT trial. Eight ML-based models were constructed, including 72 candidate variables. The C-index and DeLong test were used to assess discrimination and the improvement in discrimination between models, respectively. Calibration of the HF risk prediction model was plotted to obtain bias-corrected estimates of predicted versus observed values. Results: Least absolute shrinkage and selection operator (LASSO) Cox regression was the best-performing model for 1- and 6-year mortality, with a highest C-indices at 0.83 (95% CI: 0.68-0.94) over a maximum of 6 years of follow-up and 0.77 (95% CI 0.64-0.89) for the 1-year follow-up. The random forest (RF) showed the best discrimination for HF re-hospitalization, scoring 0.80 (95% CI: 0.66-0.94) and 0.85 (95% CI 0.71-0.99) at the 6- and 1-year follow-ups, respectively. For risk assessment analysis, Kansas City Cardiomyopathy Questionnaire (KCCQ) subscale scores were the most important predictor of readmission outcome in the HFmrEF patients. Conclusions: ML-based models outperformed traditional models at predicting mortality and re-hospitalization in patients with HFmrEF. The results of the risk assessment showed that KCCQ score should be paid increasing attention to in the management of HFmrEF patients.